H-O-S-Pb isotopes for Sources of Ore-forming Material of Yinshuisi and Gongdongchong Pb-Zn Deposits in Eastern Dabie Orogen. Issue 2 (August 2019) - Wu, Haoran; Xie, Yuling; Wang, Ying
Abstract: The Yinshuisi and Gongdongchong are two important Pb-Zn deposits of the the eastern border of Qinling-Dabie metallogenic belt, Jinzhai County, Anhui Province. δD and δ180 values for the Yinshuisi and Gongdongchong deposits are -102.‰ to -93.7‰ and -4.8‰ to -2.8‰, -85.7‰ to -74.0‰ and -1.7‰ to 0.1‰, respectively, indicating the ore-forming fluid is magmatic origin and mixed with the meteoric water. δ34S values of ore sulfides from the Yinshuisi and Gongdongchong deposits show a narrow interval of (1.7‰ to 4.4‰ and 2.4‰ to 5.3‰), suggesting sulfur in the these deposits was derived from magma. In the Yinshuisi and Gongdongchong deposit, 206 Pb/ 204 Pb, 207 Pb/ 204 Pb and 208 Pb/ 204 Pb values of sulfides point up the ore-forming metals from mixing source, mantle and crust, but not the same source. Pb isotopic compositions of the ore sulfides are close to the mineralization-related intrusions, indicating the intrusions provided major of the ore-forming material.